Plantar Ulcers and Neuropathic Arthropathies: Associated Diseases, Polyneuropathy Correlates, and Risk Covariates. (April 2019) - Andrews, Karen L.; Dyck, Peter J.; Kavros, Steven J.; Vella, Adrian; Kazamel, Mohamed; Clark, Vicki; Litchy, William J.; Dyck, P. James B.; Lodermeier, Karen A.; Davies, Jenny L.; Carter, Rickey E.; Klein, Christopher J.
ABSTRACT: OBJECTIVE: To evaluate the associated diseases, polyneuropathy correlates, and risk covariates of neuropathic plantar ulcers (PUs) and neuropathic arthropathies (NAs). DESIGN: The authors conducted a retrospective, observational study over 3.5 years of 69 patients with neuropathy, NA, or PU seen in a wound clinic who also had a comprehensive neurologic evaluation and neurophysiologic testing. Comparisons were made to a population representative cohort of patients with diabetes mellitus (DM; n = 259). RESULTS: Of the 69 wound clinic patients, 32 had PUs, 14 had NAs, and 23 had both. Of the 61 adequately assessed patients, 37 (61%) had DM, 22 (36%) had no known associated disease, and 2 (3%) had hereditary sensory and autonomic neuropathy. Of the 37 patients with DM, 35 had distal polyneuropathy, and 2 did not. In 22 patients with chronic idiopathic axonal polyneuropathy, 20 had distal polyneuropathy. CONCLUSIONS: Although DM was the disease most commonly associated with PUs and NAs, chronic hyperglycemia may not have been the major underlying risk factor. The major risk covariates are sensation loss from polyneuropathy, old age, obesity, repetitive foot injury, and inadequate foot care or treatment. Physicians and other healthcare providers can help by identifying patients at risk and instituting measures such as adequate foot care to decrease these risks.